Rekonstruksi LKPD untuk meningkatkan keterlibatan dan penguasaan konsep peserta didik pada materi sistem ekskresi - Rahmadatillah, Fauziani; Riandi, Riandi; Kusdianti, Kusdianti (Assimilation: Indonesian Journal of Biology Education, 2021)
This research was aimed at investigating the information about the use of the Student Worksheet (LKPD) the results of reconstruction about the involvement and mastery of students' concepts in the material of human excretion system. Reconstruction of student worksheets was done because the previous research shows analysis results the component of diagram vee in the eksperiment students worksheet is low. Whereas, the diagram Vee's rubric is usually used for developing eksperiment students worksheet. This research is a descriptive research. The subject of the research are 28 students of grade XI IPA in senior high school Bandung. The instrument that used is the rubric of component of diagram Vee's existence, observation worksheet in students engagement and test of mastering concept that consist is multiple choice. The result of the research shows : (1) students engagement in the class is about 79,17%; (2) students' mastery of concepts based on categories is good, 96.43% of students achieve maximum completeness criteria (KKM), and an average N-gain of 0.72. This showed the influence of use reconstruction of student worksheets on the student engagement and mastery of student concepts.